Pancala APP (Pancasila’s Character Profile): Sebagai Inovasi Mendukung Merdeka Belajar Selama Masa Pandemik - Aditia, Dimas; Ariatama, Soni; Mardiana, Emi; Sumargono, Sumargono (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
The world of education during the pandemic period showed disturbing instability, field findings stated that offline learning made students unable to absorb knowledge optimally. Other problems such as the decline in the character of students also followed. Various policy packages were launched by the government, one of which was independent learning. The purpose of this study is to reveal about: 1) Educational problems during the pandemic 2) School efforts to support independent learning 3) Media teachers in instilling values ​​in the profile of Pancasila students at SD N 1 Gedong Meneng. In this study using Research and Development (R&D). Data collection techniques used are observation, questionnaires and interviews. The data analysis technique used is by collecting data, reducing data and presenting data. The results of this study are 1) The contribution of teachers or schools in supporting independent learning. 2) School efforts in instilling the values ​​of the Pancasila student profile in students through the Android application as a fun learning supplement. 3) Creation of Pancala APP (Pancasila's Character Profile) media.